ANALYSING THE EFFECT OF CORPORATE ENVIRONMENTAL PERFORMANCE ON CORPORATE FINANCIAL PERFORMANCE: DOES A NONLINEAR RELATIONSHIP OCCUR? - Septiavin, Qori'atul; Feriansyah; Rico Ricardo; Achmad Kautsar; Eka Puspitawati; Syifa Salsabila (Journal of Central Banking Law and Institutions, 2023)
Climate change as a part of environmental degradation has become a topic widely discussed in recent decades. This study analyses the relationship between corporate environmental performance and corporate financial performance by studying cases at the company level. The company level was chosen to focus the research since companies are the main actors in economic activity as producers of both goods and services. The method used is unbalanced panel data regression with the Random Effects Model with a sample of 175 firms from 2003 to 2021 in 20 countries. This research also captures the influence of the COVID-19 pandemic. Empirical results show that there is no nonlinear relationship between corporate environmental performance and corporate financial performance with the Lind-Mehlum test. It indicates that there is a trade-off between profit and the environment. As such, the effort of businesses to drive investors from the profit-oriented to become green-oriented needs significant effort. A key policy priority should therefore be the long-term reinforcement of businesses in green activities.